2020
DOI: 10.1039/d0se01273d
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbs: treasure troves for the discovery of environmentally friendly promoters for methane hydrate formation

Abstract: Chinese herbs are rich resources for the discovery of new environmentally friendly promoters for methane hydrate formation. We demonstrated that 20 out of 300 kinds of Chinese herbs were highly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The organic anionic surfactant SDS has long been regarded as the benchmark promoter because of its excellent promoting performance on MH formation. , As shown in Figure , at a concentration of 0.20 wt %, SDS can greatly promote MH formation to reach a gravimetric capacity of 132.2 mg g –1 in 1000 min with a t 90 of around 13 min. Under the same conditions, the best promoting performance (131.8 mg g –1 with a t 90 of around 18 min) of the inorganic composite promoter on MH formation is still slightly lower than that of SDS. ,, However, MH formed by using SDS promoter produced copious and persistent foam after dissociation (right inset in Figure ) which would be a troublesome engineering problem on larger scales. , By contrast, MH that formed from the inorganic composite promoter solution dissociated without foaming under the same conditions (left inset in Figure ). It has been observed that an unusual growth of gas hydrate can occur in the presence of some kinetic inhibitors under high driving force .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The organic anionic surfactant SDS has long been regarded as the benchmark promoter because of its excellent promoting performance on MH formation. , As shown in Figure , at a concentration of 0.20 wt %, SDS can greatly promote MH formation to reach a gravimetric capacity of 132.2 mg g –1 in 1000 min with a t 90 of around 13 min. Under the same conditions, the best promoting performance (131.8 mg g –1 with a t 90 of around 18 min) of the inorganic composite promoter on MH formation is still slightly lower than that of SDS. ,, However, MH formed by using SDS promoter produced copious and persistent foam after dissociation (right inset in Figure ) which would be a troublesome engineering problem on larger scales. , By contrast, MH that formed from the inorganic composite promoter solution dissociated without foaming under the same conditions (left inset in Figure ). It has been observed that an unusual growth of gas hydrate can occur in the presence of some kinetic inhibitors under high driving force .…”
Section: Resultsmentioning
confidence: 95%
“…Under the same conditions, the best promoting performance (131.8 mg g −1 with a t 90 of around 18 min) of the inorganic composite promoter on MH formation is still slightly lower than that of SDS. 15,38,43 However, MH formed by using SDS promoter produced copious and persistent foam after dissociation (right inset in Figure 2) which would be a troublesome engineering problem on larger scales. 41,43 By contrast, MH that formed from the inorganic composite promoter solution dissociated without foaming under the same conditions (left inset in Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this, the hydrate film generally remains impermeable to the liquid. An argument favoring these assumptions is the large number of recently published studies in which the acceleration of hydrate formation and an increase in the degree of water-to-hydrate transformation have been observed in the solutions of various substances, from boric acid, amino acids, and kinetic hydrate inhibitors to brewed tea and components of tea and other herbs. , In all these cases, the solutions used for hydrate formation contained polar or ionic substances that can adsorb on the surface of hydrate particles and inhibit hydrate formation in the case of high concentrations in solutions. Thus, the promoting effect may not be related to additive chemical features but caused by the same impact both on the formation of hydrate film and properties of this film.…”
Section: Resultsmentioning
confidence: 99%